Suicide risk in a Portuguese non-clinical sample of adults - Campos, Rui C. (2015)
Background and Objectives: This exploratory study simultaneously tests the contribution of socio-demographic, clinical, distress, and personality variables for identifying suicide risk in a non-clinical sample. Methods: A convenience sample of 810 adults ranging in age from 19 to 67 years (M = 36.34, SD = 12.46) and living in various Portuguese regions participated. Their education varied from 6 to 21 years of schooling (M = 11.74, SD = 5.14). Participants responded to sociodemographic questions, the Depressive Experiences Questionnaire, the Center for the Epidemiological Studies of Depression Scale, and the Suicide Behaviors Questionnaire-Revised. Results: In the present sample, 4.3% of participants indicated past suicide attempts, 27.9% reported some lifetime suicide ideation, and 6.4% indicated a past suicide plan. Depressive symptoms, having seen a psychologist or psychiatrist, self-criticism, and education discriminated between participants who had attempted suicide (n = 35) and those who had not attempted to die by suicide (n = 775). Depressive symptoms, having seen a psychologist or psychiatrist, self-criticism, psychiatric disease and age discriminated between participants who scored below (n = 650) and who scored equal to or above (n = 160) the cut-off score for the Suicide Behaviors Questionnaire-Revised. Conclusions: Results have implications for the assessment of suicide risk.